2016
DOI: 10.2147/opth.s121256
|View full text |Cite
|
Sign up to set email alerts
|

Presence or absence of ocular surface inflammation directs clinical and therapeutic management of dry eye

Abstract: BackgroundThe presence of clinically significant inflammation has been confirmed in the tears of 40%–65% of patients with symptoms of dry eye. Ocular surface inflammation may lead to tear film instability, epithelial cell irregularities, and permeability, resulting in chronic symptomatic pain and fluctuating vision as well as negative surgical outcomes.Patients and methodsA retrospective single center medical chart review of 100 patients was conducted. All patients were tested with the InflammaDry test to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 49 publications
0
19
1
1
Order By: Relevance
“…A recent retrospective study evaluated response to CsA in InflammaDry positive and negative patients and suggested identifying dry eye patients with objective evidence of inflammation may help predict patient response to treatment. 65 …”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study evaluated response to CsA in InflammaDry positive and negative patients and suggested identifying dry eye patients with objective evidence of inflammation may help predict patient response to treatment. 65 …”
Section: Discussionmentioning
confidence: 99%
“…About 50% of these showed conversion from a positive to negative InflammaDry test, suggesting that CsA decreased MMP-9 concentration in the tears of these patients. 133 …”
Section: Csamentioning
confidence: 99%
“… 4 , 5 The presence of an inflammatory condition can be detected by the analysis of epithelial-derived inflammatory mediators, such as interleukin (IL)-1β, IL-6, and IL-8. 3 , 6 , 7 Identifying the level of ocular surface inflammation may guide therapeutic decisions, 8 allowing for more predictive and personalized therapies. 3 …”
Section: Introductionmentioning
confidence: 99%